Drastic healing process after pembrolizumab monotherapy in a case of advanced squamous cell carcinoma with severe bronchial stenosis observed over a two‐year period using continuous bronchoscopy: A case report. Issue 5 (6th March 2020) - Morikawa, Kei; Kida, Hirotaka; Handa, Hiroshi; Inoue, Takeo; Miyazawa, Teruomi; Mineshita, Masamichi
Abstract : Programmed cell death‐1 immune checkpoint inhibitor (ICI) antibody has proven to be effective in advanced non‐small cell lung cancer (NSCLC) patients positive for programmed cell death‐1 ligand‐1. However, there are currently no reports which evaluate drug efficacy by continuous bronchoscopic observation. A 75‐year‐old man with complete right atelectasis was diagnosed with squamous cell carcinoma (SCC) of the right lower lobe (tumor proportion score: TPS 90%, cT4N3M0, stage 3C). For first‐line chemotherapy, carboplatin and nab‐paclitaxel were effective for the primary lesion and the right lung atelectasis improved. However, due to repeated febrile neutropenia with pneumonia, treatment was modified to pembrolizumab monotherapy. Bronchoscopic rebiopsy prior to second‐line treatment revealed high TPS, with a severe stenosis in the right main bronchus. After three courses of pembrolizumab, the right main bronchus opened completely, and no signs of malignancy were observed. Bronchoscopic narrow‐band and autofluorescence imaging also confirmed a complete endobronchial response. Subsequent bronchoscopic observation two years after the initial diagnosis showed a complete and continued response to treatment. ICIs can result in a drastic bronchoscopic response. In this case, the healing process was notable with minimal scarring, and resulted in continued locally bronchoscopic and complete pathological response to treatment compared to previous cytotoxic chemotherapy.